The Influence of Visionary Leadership and Managerial Accountability towards Competitive Advantage - Wijayanti, Titik; Hidayatullah, Hidayatullah; Prasetiya, Benny (JURNAL AL-TANZIM, 2022)
This research is essential to measure the effectiveness of the factors that determine the competitive advantage of educational institutions. This study aims to determine the effect of visionary leadership and accountability toward competitive advantage at an educational institution. The research method used a survey; meanwhile, multiple regression tests were used to examine research hypotheses. The research samples were as many as 42 employees consisting of teachers and staff. The results of this research conclude that there is a significant influence between the visionary leadership of the headmaster and the ability to conduct accountability to competitive advantage. The coefficient score of determination shows that 88, 7 % of competitive advantage is determined by the pattern of visionary leadership and accountability. The competitive advantage of an educational institution is influenced by the principal's visioner, leadership, and accountability. The implication of this study is finding the concept that competitive advantage is influenced by visionary leadership and accountability.